Short‐chain chitin oligomers from arbuscular mycorrhizal fungi trigger nuclear Ca2+ spiking in Medicago truncatula roots and their production is enhanced by strigolactone. Issue 1 (6th February 2013) - Genre, Andrea; Chabaud, Mireille; Balzergue, Coline; Puech‐Pagès, Virginie; Novero, Mara; Rey, Thomas; Fournier, Joëlle; Rochange, Soizic; Bécard, Guillaume; Bonfante, Paola; Barker, David G.
Summary The primary objective of this study was to identify the molecular signals present in arbuscular mycorrhizal (AM) germinated spore exudates (GSEs) responsible for activating nuclear Ca2+ spiking in the Medicago truncatula root epidermis. Medicago truncatula root organ cultures (ROCs) expressing a nuclear‐localized cameleon reporter were used as a bioassay to detect AM‐associated Ca2+ spiking responses and LC‐MS to characterize targeted molecules in GSEs. This approach has revealed that short‐chain chitin oligomers (COs) can mimic AM GSE‐elicited Ca2+ spiking, with maximum activity observed for CO4 and CO5. This spiking response is dependent on genes of the common SYM signalling pathway (DMI1/DMI2) but not on NFP, the putative Sinorhizobium meliloti Nod factor receptor. A major increase in the CO4/5 concentration in fungal exudates is observed when Rhizophagus irregularis spores are germinated in the presence of the synthetic strigolactone analogue GR24. By comparison with COs, both sulphated and nonsulphated Myc lipochito‐oligosaccharides (LCOs) are less efficient elicitors of Ca2+ spiking in M. truncatula ROCs. We propose that short‐chain COs secreted by AM fungi are part of a molecular exchange with the host plant and that their perception in the epidermis leads to the activation of a SYM‐dependent signalling pathway involved in the initial stages of fungal root colonization.